Potential of Hairy Cockle’s (Anadara antiquata) Meat Extract as Antioxidant Compound - Janitra, Hadyan; Triastuti, Juni; Sulmartiwi, Laksmi (Universitas Airlangga, 2025)
Free radicals are the main factor in causing cancer and the effects of other free radicals. The role of antioxidants is very important to ward off free radicals that come from outside such as exposure to air pollution and heavy metals. Potential antioxidant activity derived from animal sources is found in shellfish. It has been reported that some types of shellfish have bioactive components. The feather mussel (Anadara antiquata) is a mussel of the same genus as the blood mussel (A. granosa) so it is likely to have almost the same content, including its bioactive components. Initial research on the bioactive components of feather mussels and their activity as antioxidants has not been carried out, so it is necessary to conduct research to find out the bioactive components that have the potential to be antioxidant compounds. The purpose of this study is to determine the presence of bioactive components and antioxidant activity in feather mussel meat extract (A. antiquata). Determination of IC50 value and test of bioactive components in feather mussel meat extract using DPPH test method. The main parameter observed was the IC50 value from testing the antioxidant activity of the hairy cockle’s meat extract. The supporting parameters observed were the yield and presence of bioactive compounds from the hairy cockle’s meat extract (A. antiquata). The results showed that the yield of clam meat extract obtained was 8.57%. There are bioactive compounds in the form of alkaloid, flavonoid, steroid, and saponin in the extract of hairy cockle’s meat. The antioxidant activity of hairy cockle’s meat extract was included in the moderate category, 102.19 μg/mL.